Prenatal Yoga Practice Increases Ferritin and MCV Levels in Pregnant Women - Farida Tandi Bara; Kartini S.; Irmayanti Oka; Eka Fadillah Bagenda; Hartati S. (Indonesian Journal of Global Health Research, 2024)
This study aimed to determine the effect of prenatal yoga practice on hemoglobin, ferritin, and MCV levels. Prenatal yoga asanas were hypothesized to have a significant impact on Hb levels. Prenatal yoga is potentially an intervention to improve iron metabolism by increasing heme synthesis in the body, and ferritin plays an important role in the relationship between prenatal yoga and hemoglobin in pregnant women. A quasi-experimental design with a pre-post test was employed. The study sample consisted of 137 pregnant women in their second trimester. Data were analyzed using the Mann-Whitney U test. The results showed no significant increase in hemoglobin levels (p=0.056), but there were significant increases in ferritin (p=0.004) and MCV levels (p=0.000). Prenatal yoga practice can maintain hemoglobin levels and increase both ferritin and MCV levels.